Antimicrobial Effects of Cassava Peel and Leaves against Oral Pathogens - Florencia L. Kurniawan; Octarina Octarina; Astri Rinanti; Komariah Komariah; Mark L. Lauw; Ilman N. Maulana (e-GiGi, 2026)
Abstract: Cassava peel and leaves (Manihot esculenta Crantz) are agro-waste materials rich in secondary metabolites with potential antimicrobial properties. Research exploring their effects against oral pathogens remains limited. This study aimed to evaluate the antibacterial and antifungal activity of cassava peel and leaf extracts against Staphylococcus aureus, Streptococcus mutans, and Candida albicans. This was a laboratory and experimental study. Samples of cassava leaves, outer and inner young peel (six months), outer and inner mature peel (10 months) were dried, powdered, and subjected to ethanol maceration. Phytochemical screening assessed flavonoids, alkaloids, saponins, tannins, quinones, steroids, and triterpenoids. Antimicrobial activity was tested using the microdiffusion well method, and inhibition zones were measured in millimeters. Positive controls were chloramphenicol (for bacteria) and nystatin (for fungi). Negative control was sterile aquadest. The results showed that leaf extract produced inhibition zones of 8.90 mm (S. aureus), 6.00 mm (S. mutans and C. albicans). Peel extracts showed varying activity, with outer young peel (6 months) yielding 7.25 mm (S. aureus), 6 mm (S. mutans and C. albicans)  and inner young peel (6 months) yielding 8.74 mm (S. aureus), 35.27 mm (S. mutans), 6 mm (C. albicans)  while outer mature peel (10 months) yielding 6.13 mm (S. aureus), 6.00 mm (S. mutans and C. albicans) and inner mature peel (10 months) yielding 10.44 mm (S. aureus), 55.36 mm (S. mutans), 6 mm (C. albicans). Phytochemical screening confirmed the presence of flavonoids, tannins, and saponins in most of cassava peel and leave samples. In conclusion, cassava peel and leaf extracts exhibit antimicrobial activity against major oral pathogens, with inner mature peels (10 months) showing the strongest effect against Streptococcus mutans. These results support their potential use as natural antimicrobial agents in herbal oral care formulations. Keywords: antibacterial; cassava peel; cassava leaves; oral pathogens; phytochemicals